2010
DOI: 10.1111/j.1540-5826.2010.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Regression Discontinuity Design in Tiered Intervention Research: A Pilot Study Exploring Vocabulary Instruction for At‐Risk Kindergarteners

Abstract: The purpose of this article was twofold: (1) to explore the feasibility of the regression discontinuity design (RDD) in response-to-intervention implementation research and (2) to expand upon the limited research on vocabulary instruction for kindergarten students who are at risk for reading failure due to limited vocabularies. This pilot study employed an abbreviated, prototypical tiered instructional model to deliver vocabulary instruction to both at-risk kindergarten students and students not at risk for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Of these, 14 received a 1‐point score (Case et al, 2010; Chambers et al, 2011; Fuchs, Compton, Fuchs, Bryant, & Davis, 2008; Kerins, Trotter, & Schoenbrodt, 2010; Loftus, Coyne, McCoach, Zipoli, & Pullen, 2010; McMaster et al, 2005; Nelson, Vadasy, & Sanders, 2011; Pullen, Tuckwiller, Konold, Maynard, & Coyne, 2010; Schuele et al, 2008; Simmons et al, 2008 , 2011; Tuckwiller, Pullen, & Coyne, 2010; Ukrainetz, Ross, & Harm; 2009; Vernon‐Feagans et al, 2010). Of these, five studies received a second score for reporting fidelity information for supplemental instruction that was provided in addition to the core reading program within Tier 1 (Loftus et al, 2010; McMaster et al, 2005; Pullen et al, 2010; Schuele et al, 2008; Tuckwiller et al, 2010). These studies received 2‐ or 3‐point ratings (one and four studies, respectively) for reporting fidelity information on a portion of Tier 1 instruction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 14 received a 1‐point score (Case et al, 2010; Chambers et al, 2011; Fuchs, Compton, Fuchs, Bryant, & Davis, 2008; Kerins, Trotter, & Schoenbrodt, 2010; Loftus, Coyne, McCoach, Zipoli, & Pullen, 2010; McMaster et al, 2005; Nelson, Vadasy, & Sanders, 2011; Pullen, Tuckwiller, Konold, Maynard, & Coyne, 2010; Schuele et al, 2008; Simmons et al, 2008 , 2011; Tuckwiller, Pullen, & Coyne, 2010; Ukrainetz, Ross, & Harm; 2009; Vernon‐Feagans et al, 2010). Of these, five studies received a second score for reporting fidelity information for supplemental instruction that was provided in addition to the core reading program within Tier 1 (Loftus et al, 2010; McMaster et al, 2005; Pullen et al, 2010; Schuele et al, 2008; Tuckwiller et al, 2010). These studies received 2‐ or 3‐point ratings (one and four studies, respectively) for reporting fidelity information on a portion of Tier 1 instruction.…”
Section: Resultsmentioning
confidence: 99%
“…The studies reported fidelity far more consistently at Tier 2 (see Table 1). In 17 of the 22 studies, detailed information on fidelity of implementation procedures and related data were provided earning a 3‐point score (Case et al, 2010; Fuchs, Compton, et al, 2008; Kamps et al, 2008; Loftus et al, 2010; Marr et al, 2011; Mathes et al, 2005; McMaster et al, 2005; Murray et al, 2010; Nelson et al, 2011; Pullen et al, 2010; Simmons et al, 2008, 2011; Tuckwiller et al, 2010; Ukrainetz et al, 2009; Vaughn et al, 2009; Vernon‐Feagans et al, 2010; Wanzek & Vaughn, 2008). For example, Case et al monitored protocol compliance in a random selection (25 percent) of audiotaped treatment sessions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have also begun to acknowledge the merit of implementing RDDs within the context of response-to-intervention literacy-focused interventions for young children (e.g., Gersten & Dimino, 2006;Tuckwiller, Pullen, & Coyne, 2010), because inherent in these interventions is a process for universal screening. The screening process presents a mechanism for providing some children more targeted intervention based on a predetermined screening cutoff, which is amenable to RDD.…”
Section: Applications In Ecsementioning
confidence: 99%